Influence of the Inappropriate School Furniture on the Bodies of Children in Development - Jevtoska, Elena; Gruevski, GJorgi (My University, 2023)
Range of activities performed in a sitting position are requiring a particular sitting angle, meaning many different positions of the body are considered as ‘sitting”. A wrongly chosen position for a particular activity may affect the curvature of the spine, can cause fatigue of the muscles on the back, on the abdomen, in the pelvis and in the femur bone, can affect the circulation in the lower extremities, and can increase pressure on the nerves affecting temperature exchange of the body. With the increase of the time spent in a sitting position and the consequences that can be brought by an incorrect sitting position, it is necessary to pay more attention when designing the chairs. The influence of the sitting position is especially expressed in the groups of users who are spending most of the time in this position while performing their daily activities. This group of users also includes children of school age spending the school day in a sitting position. If it is not carefully dimensioned and designed, the long-term use of furniture for sitting and working in educational institutions can cause harm to the health of the users. The purpose of this research is to provide data on the effect of a wrongly dimensioned chair on different height users of school furniture.
Keywords: anthropometry of children, physical development, school chairs, school desk, school furniture.